Journey through nature and self: the melancholic narrator in Atwood's Surfacing - Sedehi, Kamelia Talebian; Wan Yahya, Wan Roselezam (Universiti Putra Malaysia Press, 2015)
Julia Kristeva's melancholic subject is one who feels a sense of loss and cannot express herself openly. As a result of melancholia, the subject exhibits strange behaviour, loses her language, and isolate herself. As such, the melancholia is seen as a disorder of self-identity. It is the aim of this paper to discuss how Margaret Atwood's melancholic female subject in Surfacing goes on a quest-journey in the wilderness to deal with her sense of loss and regainsa new life. In the initial part of her life, the protagonist is seen destroying herself through a loveless union with her husband, loss of her parents, and coerced abortion. As a melancholic subject, she is unable to express and share her grief with those around her. Her expedition in search of her missing father brings about new experiences in nature which eventually leads to her self-recognition as she finds ways to deal with her condition. This reading of Atwood's female protagonist as a melancholic subject provides a new depiction of how melancholia is healed through interaction with nature.